Locus of control and job search strategies - Marco Caliendo; Deborah A. Cobb-Clark; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2010)
Standard job search theory assumes that unemployed individuals have perfect information about the effect of their search effort on the job offer arrival rate. In this paper, we present an alternative model which assumes instead that each individual has a subjective belief about the impact of his or her search effort on the rate at which job offers arrive. These beliefs depend in part on an individual's locus of control, i.e., the extent to which a person believes that future outcomes are determined by his or her own actions as opposed to external factors. We estimate the impact of locus of control on job search behavior using a novel panel data set of newly-unemployed individuals in Germany. Consistent with our theoretical predictions, we find evidence that individuals with an internal locus of control search more and that individuals who believe that their future outcomes are determined by external factors have lower reservation wages.
Keywords: J64; 330; Job search behavior; search effort; reservation wage; locus of control; unemployment duration; Arbeitsuche; Informationsverhalten; Persönlichkeitspsychologie; Anspruchslohn; Arbeitslosigkeit; Dauer; Schätzung; Deutschland